Pelaksanaan Kegiatan Pengabdian Masyarakat di Komplek Perumahan PT.BDSN Desa Tangga Batu 1 kec. Parmaksian Kab. Toba, Ramadhan 1442 H, 2021 M - Suhendri Hamzah (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2021)
Abstract In this day and age the adherents of Islam are very many, ranging from children to adults, but many are only Muslim but do not know anything about Islam, both the basics and others. Likewise in the country of Indonesia, there are many people who do not understand the basics of Islam, especially in the Toba area which is mostly Christian. Because it is really needed people who can teach the true religion of Islam well there who can help people understand Islam properly. From the above statement, a question can be drawn how to solve the problem of a lack of understanding of the correct Islam in areas with Islamic minorities? Therefore, we are conducting Field Work Lectures in the Toba area to overcome this problem, which is expected to produce satisfactory results and can help in the development of Islam in Indonesia .Keyword: Basic of Islam, minorities, Islam